On the performance of 5G for cloud- and edge-based emergency services in smart cities - Perna, Gonçalo (2021)
The deployment of emergency services in a city scenario, such as the ones for users’ safety in the roads, require the support of fast network technologies and efficient network architectures. Moreover, these services need to be available city-wide, so a flexible approach is needed to deploy high-speed technology to the overall city.This paper addresses the performance of 5G technology and its architecture to deploy emergency services with strict requirements, when compared to the use of fiber throughout the city. It considers the location of demanding services, in this specific case the people detection in the road through video cameras, both in the edge and the cloud, and with both fiber and real 5G connection between the edge and the cloud. We evaluate this architecture in a real scenario with real users and vehicles in the area. The obtained results show that 5G with an edge-based approach can provide similar services to fiber-based connections to the cloud.